Prostate-specific membrane antigen-directed imaging and radioguided surgery with single-photon emission computed tomography: state of the art and future outlook. (2nd November 2022) - Filippi, Luca; Palumbo, Barbara; Frantellizzi, Viviana; Nuvoli, Susanna; De Vincentis, Giuseppe; Spanu, Angela; Schillaci, Orazio
ABSTRACT: Introduction: Prostate-specific membrane antigen (PSMA) has emerged as a highly relevant target for prostate cancer (PC) diagnosis and therapy. PSMA inhibitors targeting PSMA-enzymatic domain have been successfully labeled with radionuclides emitting positrons or gamma-photons, thus obtaining tracers suitable for imaging with positron emission computed tomography (PET/CT) or single-photon emission tomography (SPECT). Areas covered: The different approaches for obtaining PSMA-ligands labeled with gamma-emitting nuclides ( 99m Tc or 111 In) are reviewed. Furthermore, the applications of 99m Tc/ 111 In-PSMA SPECT for the imaging of PC patients in different clinical settings (staging or biochemical recurrence) are covered. Lastly, the employment of PSMA-targeted SPECT tracers for radioguided surgery (RGS) during primary or salvage lymphadenectomy is discussed. Expert opinion: RGS provided satisfying preliminary results in both primary and salvage lymphadenectomy, allowing to discriminate between pathological and non-pathological nodes with high accuracy, although prospective studies with larger cohorts are needed to further validate this surgical approach. The potential of PSMA-targeted SPECT/CT has not been fully explored yet, but it might represent a relatively cost-effective alternative to PSMA PET/CT in limited resource environments. In this perspective, the implementation of novel SPECT technologies or algorithms, such as semiconductor-ionization detectors or resolution recovery reconstruction, will be topic of future investigation.